Application of Intracranial Pressure-Directed Therapy on Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage - Yang, Jun; Lu, Junlin; Li, Runting; Lin, Fa; Chen, Yu; Han, Heze; Yan, Debin; Li, Ruinan; Li, Zhipeng; Zhang, Haibin; Yuan, Kexin; Li, Hongliang; et al. (Frontiers in Aging Neuroscience, 2022)
Elevated ICP is a well-recognized phenomenon in aneurysmal subarachnoid hemorrhage (aSAH) that has been demonstrated to lead to poor outcomes. Delayed cerebral ischemia (DCI) is the most important reason for a poor clinical outcome after a subarachnoid hemorrhage. DCI is understood as a multifactorial process that evolves over time, largely caused by the sequelae of increased intracranial pressure (ICP). The study aimed to assess how to better define the association between ICP and DCI, and whether rational ICP management can improve the outcome of aSAH patients. Our study suggests that ICPs less than 15 mmHg possibly constitute normal values and that 28.5 mm Hg is the ICP threshold most strongly associated with the occurrence of DCI in aSAH patients. Patients who received the ICP-directed treatment presented a lower incidence of DCI. Our findings provide a basis for the recommendation of ICP-directed treatment after aSAH.